Social Role of Alms (zakāt) in Islamic Economies - Bukowski, Adam (Annales. Etyka w Życiu Gospodarczym, 2014)
Islam as both religion and socioeconomic system is based on five main pillars, thatis – five basic acts considered mandatory by Muslims, summarized in the hadith ofGabriel. One of them is zakāt (almsgiving), i.e. giving 2.5% of one’s wealth to thepoor and needy.In contrary to Christian religion, where question of charity is rather of a voluntarymatter, the role of zakāt in Islam is much more rigidly described. Almsgivingis considered as a duty of a pious Muslim towards the poor. Thus in Islamiceconomy, strongly based on Islam principles given by Allah to Muhammad, zakātis imposed by law and is not considered a charity but duty rather. The notion ofzakāt is mentioned in Qur-an over a 100 times, solely or in conjunction with othercommandments. On a basis that zakāt is to be paid as a part of total wealth exceedinggiven minimum wealth (nisab) it is then justifiable to say that zakāt isprincipally a tax.A role of this essay is to shed some light on a utilisation and role of zakāt inIslamic economies in socioeconomic context, with an example of Islamic Republicof Pakistan, where in 1980 the Zakāt Ordinance was imposed. The concept ofzakāt is present in many Islamic countries, but its nature varies, being dependentfrom the interpretation of religious law in a given country. Everywhere though, itssocial role as an important tool maintaining social justice is strongly expressed.Of course zakāt system also has its drawbacks and is subjected to much criticism.The article aims to present both advantages and negative aspects of zakāt.